Evolution of the concept of Brand Capital Value for universities - Cano Lanza, Ana María (2020)
Although there is abundant literature referring to the concept of brand, as well as regarding the creation of brand capital for products and services, there is no specific study that reviews the literature on university brand, nor models or studies on capital value creation of University brand. To address this information gap, the research brought together the main studies developed on these topics and proposes a classification of university brand definitions. Finally, given the scarce research carried out in Peru on models of university brand creation, a need to carry out a research that leads to the design of a brand capital creation model for Peruvian universities that meets the dimensions most valued by Peruvian students. in the country was evidenced.